The Process of Human Creation in The View of HAMKA With The Nazhariyyat Al-Siyaq Approach (Analysis of The Book of Al-Azhar) - Yuyun Affandi; Maljaul Abror Abdillah; Latifatul Asna; Mohammed Saad Alhuwaymil (Universitas Islam Negeri Walisongo Semarang, Indonesia, 2023)
This research tries to elaborate on the interpretation of HAMKA in his book Tafsir al-Azhar (تفسير الأزهر) on the verses of the process of human creation, especially in Q.S. Al-Mu'minun/23:1-17. Most researchers seem more inclined to approach the Kauniyyah verses from the standpoint of scientific explanation, including when interpreting verses related to the process of human creation (embryology) in Q.S. Al-Mu'minun/23:1-17. If scrutinized, HAMKA’s interpretation of these is present in disputing disbelievers' rejection of the phenomena of physical resurrection (Ba'tsu al-Ajsad) on the Day of Judgment. This study is qualitative in form and was created using a literature review using the Nazhariyyat al-Siyaq approach (نظرية السياق) to see the substance of these verses from the context of their appearance in Surat al-Mu'minun while considering the similarity of their context which exist in Chapter al-Hajj and al-Ghafir. The results of this study indicate that HAMKA interprets the verses in Q.S. Al-Mu'minun/23:1-17 by dividing them into two clusters. First, verses 1-11 are about the characteristics of a believer person. Second, verses 12-17 are about the process of human creation, which ends with a warning about the day of resurrection. HAMKA combines verses 12, 13, and 14, which discuss the process of human creation, into one cluster with verses 15-17 about the day of resurrection. In the writer's opinion, through the Nazhariyyat al-Siyaq approach (theory of context), it appears that the presence of verses 12, 13, and 14 (which talk about the process of human creation) is more of an invitation to reflect on the origin of human beings, where did they come from, how did they live and where will they return? In other words, HAMKA's interpretation of verses 12, 13, and 14 has more of an eschatological nuance (i.e., belief in the existence of a physical resurrection [ba'tsu al-ajsad] on the Day of Resurrection) rather than a scientific nuance.